PENGARUH METODE BRAINSTORMING BERBANTUAN MEDIA PEMBELAJARAN POP UP TERHADAP BERPIKIR KREATIF SISWA DALAM MATA PELAJARAN IPAS KELAS V UPT SPF SDN KOMPLEKS IKIP 1 - Darwis, Arnianti; Irfan, Muhammad; Rahman, Abdul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to determine: (1) the implementation of learning using the Brainstorming method assisted by Pop Up learning media, (2) students' creative thinking abilities before and after the treatment in the experimental class, and (3) the effect of using the Brainstorming method assisted by Pop Up learning media on students' creative thinking abilities in the IPAS subject for grade V at UPT SPF SD Negeri Kompleks IKIP 1. The research problem is based on the low creative thinking abilities of students in IPAS learning, which have not been fully facilitated through learning methods and media that encourage student activity and idea development. This research is a quasi-experimental study with a Nonequivalent Control Group Design. The research population consists of all grade V students at UPT SPF SD Negeri Kompleks IKIP 1, totaling 62 students. The research sample was determined using Purposive Sampling technique, with class VB (31 students) as the experimental group and class VA (31 students) as the control group. Research data were collected through observation of learning implementation and creative thinking ability tests in the form of pretest and posttest. Data analysis used descriptive statistics and inferential statistics with the Independent Sample T-Test. The research results show that: (1) the implementation of learning using the Brainstorming method assisted by Pop Up learning media is in the very good category, (2) students' creative thinking abilities in the experimental class improved from the sufficient category on the pretest to the high category on the posttest, and (3) the Independent Sample T-Test results indicate that the calculated t-value is greater than the t-table value at a 5% significance level. Based on these results, it can be concluded that the use of the Brainstorming method assisted by Pop Up learning media affects students' creative thinking abilities in the IPAS subject for grade V at UPT SPF SD Negeri Kompleks IKIP 1.